For the children?: protecting innocence in a carceral state - Meiners, Erica R. (University of Minnesota Press, 2016)
Introduction -- Childhoods -- Magical age -- The trouble with the child in the carceral state -- Schools and prisons -- Beyond reform: the architecture of prison and school closure -- Restorative justice is not enough -- Adulthoods -- Life and death : re-entry after incarceration -- Registering sex, rethinking safety -- After and now -- Not this: building present futures -- Acknowledgments -- Notes -- Bibliography -- Index